STRATEGY OF ECOREGION PROTECTION AND MANAGEMENT, CASE STUDY OF TASIKMALAYA CITY - Nurcholis Salman (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2021)
The Tasikmalaya City Ecoregion Protection and Management Strategy is a planning study aimed to support other developments, in accordance with the mandate of Law Number 32 of 2009 concerning Environmental Protection and Management. The purpose of this document is to provide an indication of the policy direction for environmental protection and management plans in the Tasikmalaya City based on the results of an analysis of the main challenges and strategic issues that refer to an environmental inventory at the ecoregion level in the Tasikmalaya City. The preparation of this document is intended to provide direction, reference and basis for development in the Tasikmalaya City based on the potential, availability, limitations of ecosystem services and natural resources in the Tasikmalaya City which are manifested in the threshold and status of the carrying capacity and the carrying capacity of the environment. Based on this status, policy interventions and program directions for environmental management and protection can be further formulated as a controller of development in Tasikmalaya City. The study is structured through the following stages: (1) data collection, thematic maps, and related literature, (2) Situational Analysis for the formulation of the main challenges and strategic environmental issues in Tasikmalaya City, using a spatial analysis framework, followed by DPSIR analysis (Driving Forces-Pressure-State-Impacts-Response) to identify the root causes of strategic issues of environmental protection and management, formulate their impact on community welfare and formulate policies and program directions as interventions in environmental protection and management.